World War II in the Philippines : defense, defeat and defiance - Salazar, Generoso, P. (Manila : Veterans Federation of the Philippines, 1993)
Vol.I
Keywords: World War, 1935-1945 Philippines Underground movements; World War, 1939-1945 Philippines